Numerical Investigation on the Effects of Internal Flow Structure on Ejector Performance - M. Falsafioon; Z. Aidoun; K. Ameur (Journal of Applied Fluid Mechanics, 2019)
Recent work on ejector performance enhancement indicates that more information on ejector internal flow structure is needed to have a clearer picture of factors and conditions affecting operation and performance of these devices. This paper relies on experimental studies and CFD simulations to identify flow structures occurring under typical ejector refrigeration conditions and primary nozzle geometry and position. Effects on parameter distributions and the resulting operation of the device are given particular attention. The CFD model used for this purpose was validated by using in-house data, generated from an experimental prototype and over a wide range of conditions. The experiments for the selected condition were predicted very satisfactorily by numerical model. The study then focused on the role of the primary nozzle geometry and the distance of the nozzle from the beginning of the mixing chamber (NXP), in locally shaping the flow structure and the related consequences on ejector operation. Simulations on NXP for given operating conditions have shown that an optimum value was always found, and slightly varied the operating conditions within the range considered. Primary nozzle shape changes in terms of outlet diameters for given upstream conditions directly affected the expansion level of the flow. The simulations showed that an optimum range of nozzle exit diameters could be found, for which ejector performance was highest. Moreover, under these conditions it was observed that pressure fluctuations inside the ejector were reduced.